SIMULASI PENCARIAN RUANG DI RSUP Dr. KARIADI BERBASIS MULTIMEDIA INTERAKTIF (Information Technology and Telematics, 2014)
Abstrac This study began when advances in technology are developing very rapidly, one that is both that health-related treatment or for the quality of hospital care. RSUP Dr. Kariadi has a number of rooms very much, therefore this study want to aim how to program an application to search the room quickly. In the research method used is a multimedia development methods that interact with users. Make it easier to manufacture and maximum results in this study using adobe flash as software. In the flash we can create more animated when compared to other applications. But with limited time, this study is only intended as a simulation, so I'll just take a sample of some of the room alone. The results of this study show that animation is the direction toward which the room indicated by the directional arrows that run automatically. Keywords: multimedia, flash, simulation